A study of the material in the ATLAS inner detector using secondary hadronic interactions - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acerbi, E; et al. (2012)
The ATLAS inner detector is used to reconstruct secondary vertices due to hadronic interactions of primary collision products, so probing the location and amount of material in the inner region of ATLAS. Data collected in 7 TeV pp collisions at the LHC, with a minimum bias trigger, are used for comparisons with simulated events. The reconstructed secondary vertices have spatial resolutions ranging from ∼ 200μm to 1 mm. The overall material description in the simulation is validated to within an experimental uncertainty of about 7%. This will lead to a better understanding of the reconstruction of various objects such as tracks, leptons, jets, and missing transverse momentum. © 2012 CERN.